Performance of omnichannel warehouse of Muslim fashion company in Indonesia based on workforce, equipment, space, and information system aspects - Vita Sarasi; Iman Chaerudin; Fadila Nurfauzia (Cogent Social Sciences, 2024)
The objective of this study is to determine the overall effectiveness of omnichannel warehouses, with a focus on the fashion industry, which has demonstrated resilience during the pandemic by utilizing both offline and online sales techniques. This study essentially develops a generic technique for evaluating omnichannel warehouse productivity based on the design of Karim et al., adjusting some of its indicators to suit Indonesia’s medium-sized fashion industry. The observational study’s results indicate that the workforce and space categories’ Key Performance Indicators (KPIs) for the fashion sector are still deficient. Based on discussions with various management entities, it is suggested that KPIs be extended into four categories by including measures related to space and information systems. Moreover, four indicators—product receiving, identification, and picking (offline) in the labor category, and transportation utilization in the space category—are highlighted using the Traffic Light System (TLS) method as the highest priority areas for improvement. The fundamental reasons for these issues are found through fishbone diagram analysis, and they include a deficient fleet of vehicles, imprecise transportation plans, inaccurate demand projections, insufficient employee training about new products, and inadequate mechanisms for communication between the sales, warehouse, and vendors. The limitation of this study is that it solely looked at the fashion industry’s productivity. It is recommended that future studies use omnichannel principles across many businesses to measure other industry variables like time, cost, and quality.